CBMS-03 PHOSPHORYLATION STATE OF OLIG2 REGULATES PROLIFERATION OF GLIOMA STEM CELLS. (16th December 2019) - Saito, Norihiko; Hirai, Nozomi; Aoki, Kazuya; Sato, Sho; Suzuki, Ryo; Hiramoto, Yu; Fujita, Satoshi; Nakayama, Haruo; Hayashi, Morito; Sakurai, Takatoshi; Iwabuchi, Satoshi
Abstract: The Cancer Genome Atlas project described a robust gene expression-based molecular classification of glioblastoma with the functional and biological significance of the subclasses yet to be determined. Here, we show that a comprehensive analysis of a panel of glioma initiating cell (GIC) lines can identify a group of stem cells with high OLIGg2 expression as in Proneural-like GBM subtype. In vitro differentiation studies showed that proneural GIC lines possess the potential to differentiate into astrocytic, neuronal, and oligodendrocytic lineages, whereas mesenchymal GICs exhibited limited potential for neural lineage differentiation following retinoic acid induction. A considerable decline of OLIG2 in proneural GIC lines was observed following retinoic acid treatment. We also showed that OLIG2 is a functional marker associated with cell proliferation in Olig2-high GIC lines. In addition, OLIG2 inhibition disrupted cell-cycle control mechanism by decreasing CDK2 and CDK4 and elevating apoptosis-related molecules. Mechanistic investigations revealed molecular interactions between CDK2/CDK4 and OLIG2. Inhibition of CDK2/CDK4 activity disrupted OLIG2-CDK2/CDK4 interactions and attenuated OLIG2 protein stability. Further investigation on these mechanisms may lead to novel targeted therapy on GBMs with high OLIG2 expression.